Psychological distress during COVID-19 among pregnant women attending antenatal outpatient department at tertiary hospital (Journal of Patan Academy of Health Sciences, 2021)
Introduction: It is known that a pregnant person’s body is undergoing immune system changes and is not operating the same way as a non-pregnant person’s body, which threatens the emotional states of women trying to cope with the COVID-19 pandemic situation. The present study aimed to identify the psychological distress during COVID-19 among pregnant women.Method: A cross-sectional analytical study was conducted at the antenatal outpatient department of Patan Hospital, Nepal. The non-probability purposive sampling technique was used to select 457 samples. Ethical approval was obtained. Data were collected through a face-to-face interview using the Coronavirus Anxiety Scale (5 items) and the Edinburgh Postnatal Depression Scale (10 items). Descriptive and inferential statistics were used for analyzing the data.Result: The average age of the respondents was 27 years. Results revealed that only 5(1.1%) pregnant women had anxiety, while 23(5.0%) had possible depression due to COVID-19. None of the sociodemographic variables were significantly associated with psychological distress (anxiety and depression) among pregnant women.Conclusion: Psychological distress was found to be minimal among pregnant women attending antenatal OPD in Patan Hospital.